Artificial Intelligent Methods for Handling Spatial Data Fuzzy Rulebase Systems and Gridded Data Problems - Verstraete, Jörg.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides readers with an insight into the development of a novel method for regridding gridded spatial data, an operation required to perform the map overlay operation and apply map algebra when processing spatial data. It introduces the necessary concepts from spatial data processing and fuzzy rulebase systems and describes the issues experienced when using current regridding algorithms. The main focus of the book is on describing the different modifications needed to make the problem compatible with fuzzy rulebases. It offers a number of examples of out-of-the box thinking to handle aspects such as rulebase construction, defuzzification, spatial data comparison, etc. At first, the emphasis is put on the newly developed method, and additional datasets containing information on the underlying spatial distribution of the data are identified. After this, an artificial intelligent system (in the form of a fuzzy inference system) is constructed using this knowledge and then applied on the input data to perform the regridding. The book offers an example of how an apparently simple problem can pose many different challenges, even when trying to solve it with existing soft computing technologies. The workflow and solutions to solve these challenges are universal and may therefore be broadly applied into other contexts.
Introduction -- Problem Description and Related Work -- Concept -- Fuzzy Rulebase Systems -- Parameters and most Possible Ranges -- Rulebase Construction -- Constrained Defuzziﬁcation -- Data Comparison -- Experiments -- Conclusion.
Keywords: Computational intelligence; Data mining; Artificial intelligence; Geographic information systems; Computational Intelligence; Data Mining and Knowledge Discovery; Artificial Intelligence; Geographical Information System